2003
DOI: 10.1002/aoc.404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tributyltin(IV) chloride on the gametes and fertilization of Ascidia malaca (Ascidiacea: Tunicata)

Abstract: Ascidia malaca gametes before fertilization incubated in 10 À5 or 10 À7 M solutions of tributyltin(IV) chloride, TBTCl, for 3 h appear highly damaged under transmission electron microscopy observation. Also, the fertilization process is affected by the compound: the damaged spermatozoa are present in the vitelline coat and the egg does not cleave. An increase of microbodies, structurally similar to peroxisomes, have been detected in the egg peripheral cytoplasm, probably in relation to their role in alleviatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…6 In the present research, the ultrastructural aspects of fertilization in S. plicata are examined in order to compare the resistance of this species against the pollutant and to extend the study of the fertilization process using SEM. The most relevant alterations, in relation to incubation time, are observed in the follicle cells and the vitelline coat: a few follicle cells are present with a very elongated shape and the vitelline coat is highly damaged until breakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In the present research, the ultrastructural aspects of fertilization in S. plicata are examined in order to compare the resistance of this species against the pollutant and to extend the study of the fertilization process using SEM. The most relevant alterations, in relation to incubation time, are observed in the follicle cells and the vitelline coat: a few follicle cells are present with a very elongated shape and the vitelline coat is highly damaged until breakage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies of metabolic alterations in the Ciona intestinalis female gonad cells incubated in 10 −5 or 10 has shown that the eggs and the spermatozoa are highly affected and that fertilization does not occur: the spermatozoa arrest in the vitelline coat. 6 There is, at present, no well-established study that permits the appraisal of contaminant effects applicable to any species. The aim of this work is to extend analyses of effects of TBT to another species of ascidians in order to compare variation in the incidence of impact of contaminant exposure among different species, by means of scanning and transmission electron microscopy observations.…”
Section: Introductionmentioning
confidence: 99%
“…Mansueto et al 35 and Villa et al 36 Even if the 10 −5 M solution could be higher than those of the environmental antifouling coating found in the aqueous environment, many researchers have shown that the toxic effect on many processes of different species are dose and time dependent: 24,25,32 -36 the permanence of gametes, embryos and larvae in polluted environments varies in different species and consequently their integrity could be compromised in relation to the incubation time. In addition, it is known that the sediments accumulate organotin compounds and these can be remobilized and resuspended.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ascidians (or tunicates) have attracted much interest as sentinel organisms for the assessment of environmental pollution by organometallic derivatives, particularly TBT (Mansueto et al 1989;Cima et al 1996;Patricolo et al 2001;Puccia et al 2001;Mansueto et al 2003;Villa et al 2003;Puccia et al 2005;Cangialosi et al 2009Cangialosi et al , 2010Zega et al 2009;Mansueto et al forthcoming). Ascidians have a world-wide distribution with a filter-feeding behavior rendering them susceptible to pollutant bioaccumulation.…”
Section: Introductionmentioning
confidence: 99%